DOMINANSI MAJELIS TAKLIM: MENAKAR TRANSFORMASI PAHAM RADIKALISME - Ashadi L. Diab; Asni Asni; Andi Yaqub (Zawiyah: Jurnal Pemikiran Islam, 2021)
Majlis ta'lim as the gateway for Islamic education that must face the problems that arise due to the development of an increasingly globalized world, is required to continue to improve its quality so that it can play a bigger role in bridging the gap between the real conditions of Muslims, so that it is reflected and realized a knowledge and Islamic social action. The process is ideally balanced with mental and character cultivation that enables the members of the assembly to be able to face life's problems. Mental and character that has been internalized within will become whole and unified in the soul, thus forming personal integrity. The notion of radicalism which leads to terrorism is an important understanding for the people in the city of Kendari. Community contact with radicalism is certainly not something that appears by itself in the midst of society. The notion of radicalism arises because of the communication process of conversations with others, both discussions about politics, economics, and various things, especially discussions about the understanding of religion which recently have very sharp differences and one of the places where religious understanding is studied is the Taklim Council. This study uses a qualitative method with a descriptive analytical approach. Data sources are primary and secondary data sources. Data collection methods used are observation, interviews and documentation with sampling techniques. This study shows three stages in dealing with the understanding of radicalism through the taklim assembly, first starting with the form of conciliation with the materials presented later by the taklim board administrators, so that it is not only jihad material through suicide bombings but studies that are mutual respect and respect between each other, especially inter-religious people. Second, the approach of the Taklim Council towards Radicalism is through reforming the assembly which is not known by the MUI management, both city and provincial administrators. Third, involve stakeholders and related agencies who are concerned about eradicating terrorism and radicalism.